Chemical transformations at the nanoscale: nanocrystal-seeded synthesis of β-Cu2V2O7 with enhanced photoconversion efficiencies. Issue 25 (7th June 2018) - Gadiyar, Chethana; Strach, Michal; Schouwink, Pascal; Loiudice, Anna; Buonsanti, Raffaella
Abstract : Nanocrystal-seeded synthesis relies on the reaction of nanocrystal seeds with a molecular precursor and it can be regarded as the link between sol–gel and solid-state chemistries. Abstract : Nanocrystal-seeded synthesis relies on the reaction of nanocrystal seeds with a molecular precursor and it can be regarded as the link between sol–gel and solid-state chemistries. This synthesis approach aims at accessing compositionally complex materials, yet to date its full potential remains unexploited. Herein, surface oxidized Cu nanocrystal seeds with diameters from 6 nm to 70 nm are reacted with vanadium acetylacetonate to form β-Cu2 V2 O7 with a tunable grain size ranging from 29 nm to 63 nm. In situ X-ray diffraction measurements evidence the occurrence of a solid-state reaction between the NC seeds and the vanadium oxide formed during the annealing. The variation of the ion diffusion lengths, the homogeneity of the precursor solution and the number of nucleation sites with the NC seed size explains the lower formation temperature, the smaller grain size and the higher grain size monodispersity of β-Cu2 V2 O7 as the seed size decreases. Finally, the tunability afforded by the nanocrystal-seeded synthesis provides a unique opportunity to correlate the photoelectrochemical performance with the grain size in a size regime close to the charge carrier diffusion length of β-Cu2 V2 O7 (20–40 nm). The net photocurrent density peaks when the grain size is 39 nm by reaching 0.23 mA cm −2 at 1.23 V vs. RHE in the presence of a hole scavenger. While still far from the theoretical limit, this result overcomes the current state-of-the-art for β-Cu2 V2 O7 . An interesting double fold increase in the photocurrent is found in mixed phase β-Cu2 V2 O7 /CuV2 O6 samples, suggesting that nanostructuring and heterostructuring are beneficial to the performance.